Differences in ultra-endurance exercise in performance-matched male and female runners - Speechly, D. P.; Taylor, S. R.; Rogers, G. G. (Medicine & Science in Sports & Exercise, 1996)
Males (N = 10) and females (N = 10) were matched for marathon performance times. Performances were compared at 10, 21.1, 42.2, and 90 km. Only at 90 km was there a difference with females being significantly better. At all distances females worked at a higher fraction of VO2max than males. At the completion of the 90 km race, plasma free fatty acids in females were half as high as in males. During the race, females worked at approximately 60% of VO2max while males performed at 50%. These data show that females: (a) use more lipids in ultra-endurance activities than males, (b) sustain a higher work rate in terms of VO2max, (c) and possibly have a stronger disposition of sustain "hard work" levels. These data do not show that females will eventually outperform males. Implication. Women are particularly suited to long and ultra-distance events and their performance characteristics are as good as and often better than males of similar performance levels.